Bioengineered polyester nanoparticles for the synergistic treatment of androgenic alopecia via the suppression of 5α-reductase and knockdown of androgen receptor - Chen, Xiangru; Yan, Peiyu; Zhang, Wenqiang; He, Xin; Jiang, Rihua; Li, Yulin; Sun, Jing; Jiang, Jinlan (Frontiers in Bioengineering and Biotechnology, 2022)
Androgenic alopecia (AGA) is a common disease that negatively affects patients’ physical and mental health. AGA can be treated with drugs that improve the perifollicular microenvironment, such as 5α-reductase inhibitors (e.g., dutasteride [DUT]), androgen receptor blockers, and minoxidil. However, the efficacy of these treatments is limited. Therefore, this study aimed to to show that nanoparticles are effective as stable carriers with high curative benefits and little adverse effects. The in vitro study showed that PLGA-DUT/siAR@DPCM NPs could deliver both DUT and siAR to dermal papilla cells. They could successfully suppress 5α-reductase and knock down androgen receptor, respectively, and thereby promote cell proliferation. In the in vivo study, PLGA-DUT/siAR@DPCM NPs showed a significant therapeutic effect in an AGA mouse model. They successfully penetrated the stratum corneum and showed a clear targeting effect on hair follicles and surrounding tissues. PLGA-DUT/siAR@DPCM NPs could enable the targeted delivery of DUT and siAR through percutaneous penetration, enhancing phagocytosis and decreasing adverse effects. Thus, they have great potential in the clinical treatment of AGA.